DIFFICULTIES IN LEARNING FOREIGN LANGUAGES - Ibrohimov , Qobiljon; Jaloldinov , Islomiddin (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This   article   discusses    the   main   difficulties   encountered   in    the process     of    learning    foreign   languages.   In    particular,   problems   related   to  vocabulary, grammar,    pronunciation,   and   motivation   are   analyzed.    Additionally,    possible   ways    to   overcome   these   challenges  are   briefly   considered.